2019
DOI: 10.1109/lpt.2019.2921934
|View full text |Cite
|
Sign up to set email alerts
|

Outage Probability Due to Intercore Crosstalk in Dual-Core Fiber Links With Direct-Detection

Abstract: The outage probability (OP) in short-haul directdetection (DD) optical links supported by weakly-coupled multicore fiber (MCF) impaired by intercore crosstalk (ICXT) and using on-off keying signaling is assessed theoretically and through simulation. A closed-form expression for the OP is proposed for a single interfering core. This expression is useful to provide fast and reliable performance estimates in preliminary studies of weakly-coupled MCF-based systems where the ICXT is highly correlated along the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 14 publications
2
27
2
Order By: Relevance
“…It can be concluded that the walk-off has no influence on the CBI, because the walk-off has no effect on the characteristics of A XT ,x in (2). This seemingly contradicts the conclusion in [20], which states that significantly different IM/DD system performance can be observed for low and high walk-offs. The reason is that the OC-SXT term is the main XT component in [20] because the same OC's optical frequency of the lasers.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…It can be concluded that the walk-off has no influence on the CBI, because the walk-off has no effect on the characteristics of A XT ,x in (2). This seemingly contradicts the conclusion in [20], which states that significantly different IM/DD system performance can be observed for low and high walk-offs. The reason is that the OC-SXT term is the main XT component in [20] because the same OC's optical frequency of the lasers.…”
Section: Discussioncontrasting
confidence: 70%
“…This seemingly contradicts the conclusion in [20], which states that significantly different IM/DD system performance can be observed for low and high walk-offs. The reason is that the OC-SXT term is the main XT component in [20] because the same OC's optical frequency of the lasers. But the OC-OCXT term is dominant XT component in Fig.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The DP-DCM has been developed to keep the complexity and time of simulation of ICXT at acceptable levels. In such a model, the evolution of the ICXT impact on the system performance is evaluated in time fractions with a much shorter duration than the ICXT decorrelation time [20]. Those time fractions are separated by time intervals longer than the decorrelation time of ICXT.…”
Section: Mcf Modeling and Icxt Generationmentioning
confidence: 99%
“…Therefore, the evaluation of the system outage, through the outage probability (OP) metric, is of utmost importance to assess the performance of IM-DD links supported by MCFs. The ICXT impact on the OOK system performance has been assessed by comparing experimental and simulated BERs and OPs in weakly-coupled MCFs [19] and by comparison with theoretical results [20]. The dependence of the OP due to ICXT on several parameters and features of OOK systems, such as the laser linewidth [21], skew-symbol rate product [21,22], and ICXT level [19,22] has been studied.…”
Section: Introductionmentioning
confidence: 99%